âPENGARUH PERSEPSI ETIS, PENGALAMAN AUDITOR, TEKANAN KETAATAN DAN KOMPLEKSITAS TUGAS TERHADAP KUALITAS AUDIT JUDGMENTâ - Dea Bilgis Pangesti, 14.05.52.0189; Setyowati, Widhy (Students Journal of Accounting and Banking, 2018)
This research aims to determine and assess the influence of ethical perceptions, experience auditor, pressure of obedience and the complexity of the task of audit quality judgment. The independent variables in this study are ethical perceptions, auditor experience, compliance pressure, and task complexity. The population of this study is all auditors who work at Public Accounting Firm in Semarang. Sampling is done by using purposive sampling method and the number of samples as much. The primary data retrieval method used is questionnaire. This research data analysis methods using the multiple linear regression analysis by SPSS 24.0. The results showed significant and significant ethical perceptions on audit quality assessment, then the pressure of negative and significant compliance to audit assessment. Audit experience and complexity of negative audit tasks are not significant to the quality of audit judgment.Keywords: Â Â Â Â Â Audit Quality Judgment, ethical perceptions, auditor experience, pressure of obedience, task complexity